A consensus ranking based proposal for combining data in adjustment of the fundamental physical constant values; Testing, Diagnostics & Inspection as a comprehensive value chain for Quality & Safety - Muravyov (Murav’ev) S. V. Sergey Vasilyevich (2019, 2019)
Title screen